2005
DOI: 10.1186/1471-2474-6-40
|View full text |Cite
|
Sign up to set email alerts
|

The clubfoot assessment protocol (CAP); description and reliability of a structured multi-level instrument for follow-up

Abstract: BackgroundIn most clubfoot studies, the outcome instruments used are designed to evaluate classification or long-term cross-sectional results. Variables deal mainly with factors on body function/structure level. Wide scorings intervals and total sum scores increase the risk that important changes and information are not detected. Studies of the reliability, validity and responsiveness of these instruments are sparse. The lack of an instrument for longitudinal follow-up led the investigators to develop the Club… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 34 publications
0
32
0
Order By: Relevance
“…An ideal classification system should be practical and reproducible (8,9). It should consider the 3-dimensional characteristics of the clubfoot deformation and also be simple enough to be implemented in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…An ideal classification system should be practical and reproducible (8,9). It should consider the 3-dimensional characteristics of the clubfoot deformation and also be simple enough to be implemented in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…It offers a framework for describing the interactive effects of functioning, personal activities, social participation, and environmental influences [1]. Among its important features is the potential to standardize communication within the classification scheme across disciplines, assessment tools, and continents [82]. The ICF has been used to create health assessment tools [82 -84] and to identify components in other existing tools that are ICF-related [9,78,83 -90].…”
Section: Ethnic and Racial Minorities With Mobility Limitationsmentioning
confidence: 99%
“…In previous studies, the CAP has been shown to have moderate-to-good reliability and to be valid for use in follow-up of clubfoot (Andriesse et al 2005(Andriesse et al , 2006. 20 items divided into body/function structures (4 domains) and activity levels (two domains) according to the International Classification of Function, Disability and Health (ICF, World Health Organization 2000) form the CAP (Table 1).…”
Section: Clubfoot Assessment Protocol (Cap)mentioning
confidence: 99%
“…Furthermore, assessment instruments used in clinical studies should have documented reliability and validity, ensuring that these instruments have acceptable methodological quality. Our own literature search on clubfoot instruments using Medline showed that there have been very few studies focusing on reliability and validation (Maffulli et al 1997, Flynn et al 1998, Roye et al 2001, Wainwright et al 2002, Andriesse et al 2005, Celebi et al 2006, Munshi et al 2006, Andriesse et al 2006. This is still an area in need of further development.…”
mentioning
confidence: 99%
See 1 more Smart Citation